Exploring expected roles and responsibilities of waste pickers and homeowners in the waste picker integration process: a case study - Fraser, Sally (Department of Environmental and Geographical Science, 2025)
Informal waste collection in South Africa is carried out by some of society's most vulnerable individuals. Their work often operates in middle- and upper-class areas, where many homeowners have been found to hold negative perceptions towards street waste pickers and their work. In this relationship, homeowners have the ability to not allow waste pickers to access recyclables by withholding waste or closing off communities to waste pickers. Recently, it has become an important aspect of advocacy for waste picker integration in South Africa to include waste pickers in formal waste collection systems and the overall recycling value chain. This would involve including waste pickers in planning and decision-making and as active stakeholders in these two systems. The tension found in the relationship between waste pickers and homeowners is a potential barrier to waste picker integration, and could go as far as to exclude waste pickers from waste management systems and the recycling chain entirely. The perceptions and expectations of both waste pickers and homeowners of what roles and responsibilities each party plays in contributing to waste systems could offer insight into how a more effective integration process can be brought about. This study focuses on the relationship between waste pickers and homeowners in an uppermiddle-class area of Cape Town, and what perceptions and expectations there are between the two groups. An exploratory qualitative with some quantitative aspects was the approach with a case study design was used for this research. The sample was made up of 15 homeowners and 15 waste pickers, with the homeowners receiving a different questionnaire than the waste pickers. The data collection was done through a phased participatory approach. Both groups first participated in an unstructured questionnaire, which then informed the semi-structured questionnaires used in the interviews with participants. The data was then analysed through a thematic analysis and a framework of social constructionism, identifying the common themes used by both groups to frame their perceptions and expectations of informal waste collection and their relationship with the other group. Four main themes emerged from the data, namely: motivation for waste picking and recycling; experiences of vulnerability; solutions; and appreciation. It was found that some of the greatest barriers to integration could be contrasting motivations for recycling between the two groups, and the lack of a communication and knowledge sharing pathway between the groups. Opportunities for improved integration could be to explore effective communication pathways between the groups.